A review on biomass pyrolysis models: Kinetic, network and mechanistic models. (April 2019) - Hameed, Samreen; Sharma, Abhishek; Pareek, Vishnu; Wu, Hongwei; Yu, Yun
Abstract: Pyrolysis converts biomass into liquid, gaseous and solid fuels. This work reviews the existing models for biomass pyrolysis, including kinetic, network and mechanistic models. The kinetic models are based on the global reaction mechanisms and have been extensively used for a wide range of biomass under various operating conditions. Major emphases have been on the network models as these models predict the structural changes during biomass pyrolysis. Key aspects of various network models include reaction schemes, structural characteristics and applications to CFD simulations. Recent advances in understanding reaction mechanisms using mechanistic models have been summarized. Importance of inherent inorganic species in biomass pyrolysis is also critically analysed. Future studies of biomass pyrolysis modelling should focus on developing multiscale models considering reactions of all biomass components (i.e., cellulose, hemicellulose, lignin, inorganic species and extractives) and potential interactions. Highlights: Kinetic modelling for biomass pyrolysis has been reviewed. Network models for biomass decomposition have been discussed. Mechanistic models to understand pyrolysis mechanism have been reviewed.